2022
DOI: 10.3390/ijms23084394
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic Materials on the Base of Polymer Interpenetrating Networks Microgels and Benzalkonium Chloride

Abstract: Polymer microgels, including those based on interpenetrating networks (IPNs), are currently vastly studied, and their practical applications are a matter of thriving research. In this work, we show the perspective for the use of polyelectrolyte IPN microgels either as scavengers or carriers of antiseptic substances. Here, we report that poly-N-isopropylacrylamide/polyacrylic acid IPN microgels can efficiently absorb the common bactericidal and virucidal compound benzalkonium chloride. The particles can form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Being introduced into a polymer-gel matrix, the molecules of a disinfectant can be gradually released over extended periods, providing a long-term antiseptic activity [19,[30][31][32][33][34]. It was shown that the presence in the gel of units with a charge opposite to that of the disinfectant increases its load significantly and favors prolonged release [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being introduced into a polymer-gel matrix, the molecules of a disinfectant can be gradually released over extended periods, providing a long-term antiseptic activity [19,[30][31][32][33][34]. It was shown that the presence in the gel of units with a charge opposite to that of the disinfectant increases its load significantly and favors prolonged release [30].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts are directed toward the development of antiseptic systems based on polyelectrolyte gels and oppositely charged disinfectants [19,[30][31][32][33][34]. For example, Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most powerful features for the enhancement of the microgel applicability is the incorporation of various functional groups into the microparticle polymer network. Functional groups can bear charges further employed in the formation of polyelectrolyte complexes, , act as antibacterial and antiseptic substances, and serve as a conjugation site for a number of target molecules. Of course, the question of spatial availability of these groups is of importance, and that depends on the microgel’s characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…There are many applications for microgels in different areas, such as optics, coating, medicine, agriculture, actuators, etc. [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Most of the reports dedicated to microgels prepared via the self-assembly mechanism observed in precipitation polymerization used poly( N -isopropylacrylamide) (PNIPAM) as a main component [ 6 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%